Competitividade internacional e a criação de um ambiente que a favoreça - Velloso, João Paulo dos Reis (Nova Economia, 2013)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--> Competitividade internacional e a criação de um ambiente que a favoreça <!--[if gte mso 10]> <![endif]-->